Transportation security - Bragdon, Clifford R. (Butterworth-Heinemann homeland security series, 2008)
Insecure transportation systems are costing our worldwide mobility-based economy as much as 6 per cent of GDP annually. This title examines this problem in a comprehensive manner and addresses security-based technologies and solutions to minimize risk. It covers air, sea, roadway, rail and public transport modes.